2014
DOI: 10.1186/1475-2891-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for integration into the local health system of community-based management of acute malnutrition in children under 5 years: a qualitative study in Bangladesh

Abstract: BackgroundAcute malnutrition is a major cause of death among under-five children in low- and middle-income countries. United Nations agencies recommend the integration of community-based management of acute malnutrition (CMAM) into the local health systems for sustainability. The objective of the study was to assess the preparedness of the health system to implement CMAM targeting children under-five years in two sub-districts of Bangladesh.MethodsThe assessment was performed through direct observation of 44 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…Country instability, poverty, low maternal education, drought, poor nutrition governance policy, lack of service delivery and supply, poor referral, monitoring and supervision mechanism are known to contribute to high defaulter rates in these communities. 26,27 The current study had revealed significant association between high defaulter rate and children aged less than 24 months (Chi(2); 4.441, df;1, and p = 0.025). No significant association was found between gender, residency of children, distances of SAM children to OTP centre, parent education; whether mother can read or not and overall cure and defaulter rates.…”
Section: Discussionmentioning
confidence: 52%
“…Country instability, poverty, low maternal education, drought, poor nutrition governance policy, lack of service delivery and supply, poor referral, monitoring and supervision mechanism are known to contribute to high defaulter rates in these communities. 26,27 The current study had revealed significant association between high defaulter rate and children aged less than 24 months (Chi(2); 4.441, df;1, and p = 0.025). No significant association was found between gender, residency of children, distances of SAM children to OTP centre, parent education; whether mother can read or not and overall cure and defaulter rates.…”
Section: Discussionmentioning
confidence: 52%
“…Malnutrition is involved in half of the deaths of under-five children as in many developing countries (Camille et al). 9 In Egypt, malnutrition is a major health problem as 5.5% of underfive children are underweight, 8.4% are wasted and 21.4% are stunted.…”
mentioning
confidence: 99%
“…Strategi jangka pendek terdiri dari memperkuat koordinasi pemerintah dalam intervensi gizi, mengeksplorasi sumber pendanaan tambahan, melengkapi kebutuhan pusat kesehatan di pedesaan, melatih petugas kesehatan dan secara aktif dan melibatkan masyarakat untuk mengatasinya. 18 Berdasarkan beberapa penekanan dari instansi terkait tersebut maka dapat dideskripsikan bahwa masing-masing program di dinas berjalan sendiri-sendiri. Selain itu minimnya jumlah SDM yang menjadi petugas lapangan yang turun langsung ke desa masih menjadi isu utama.…”
Section: Pembahasanunclassified